Human adaptability in a Quechua population of the peruvian central Andes (Huancavelica, 3680m). Relationships between forced vital capacity, chest dimensions and hemoglobin concentration - Tarazona-Santos, Eduardo; Pastor, Santiago; Cahuana, Ronald; Pettener, Davide (Acta Andina, 2025)
The study aims to provide original data on a Quechua population froom a less studied area, the Peruvian Central Andes, and to investigate the relationships between variables involved in human adaptability to high altitude. A sample of 77 healthy unrelated adult males, natives of the Province of Huancavelica (3680 m), was examined. The following somatometric and physiometric variables were investigated: height, sitting height, weight, chest breadth, chest depth, maximum, minimum and normal chest circumferences, forced vital capacity (FVC) and hemoglobin concentration (Hb). Values of the examined variables are comparable to those from previous studies of Andean high altitude populations. Hb and age are not correlated. In order to evaluate the relationships between the variables, stepwise multiple regression analysis of FVC on the other variables was performed. Results suggest that age and respiratort mechanics, but not chest dimensions, are strongly associated with lung functionality.